Avaliação do atributo acesso aos serviços saúde na visão dos usuários e profissionais nas Unidades Básicas de Saúde em São José de Ribamar-MA - SILVA, Cristiane Alves (2019)
Introduction: Primary health care is the gateway to health care, but there are several obstacles to its functioning as advocated. Through this scenario the health assessment presents itself as a device that assists in the consummation of the proposed parameters. Objective: To analyze the presence and extension of the access attribute in Primary Health Care in the municipality of. Through PCATool. Methods: Professionals and users of the ESF of São José de Ribamar - MA responded to the primary care assessment instrument (PCATool). Results: The use of services (score 3.3) presents a better evaluation than accessibility (score 2.2), motivated by the low evaluation of indicators such as the functioning of the units at weekends and night care. There was a divergence in the evaluation of professionals and users, since professionals tend to be more condescending with the service offered. Conclusion: Identifying needs and proposing improvements in the conditions of access to primary health care means strengthening the role of primary health care as a regulator of health care.